2019
DOI: 10.1155/2019/8742363
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Frailty Survival Model for Multidrug-Resistant Tuberculosis Mortality in Amhara Region, Ethiopia

Abstract: Tuberculosis (TB), a disease caused by Mycobacterium tuberculosis (MTB), is the main cause of death. It disproportionally affects those living in the different regions of countries and within the region. The aim of this study was to examine spatial variation of mortality and the risk factor of death on multidrug-resistant tuberculosis patients treated in different MDR-TB hospitals of Amhara region. The data for this study was used from multidrug-resistant tuberculosis patients' record charts and analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…The proportion of mortality among all patients treated for MDR/ RR-TB was reported by 12 studies (Alene et al, 2017;Woldeyohannes et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018). Data were extracted from these studies by defining mortality as any death after the start of anti-TB treatment for MDR/RR-TB due to any cause in the TICs in Ethiopia.…”
Section: The Pooled Incidence Of Mortalitymentioning
confidence: 92%
See 4 more Smart Citations
“…The proportion of mortality among all patients treated for MDR/ RR-TB was reported by 12 studies (Alene et al, 2017;Woldeyohannes et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018). Data were extracted from these studies by defining mortality as any death after the start of anti-TB treatment for MDR/RR-TB due to any cause in the TICs in Ethiopia.…”
Section: The Pooled Incidence Of Mortalitymentioning
confidence: 92%
“…Then, 347 articles were screened by title and abstract. The full-text screening was conducted for 58 articles, and 17 articles that fulfilled the eligibility criteria were included in the final analysis (Ketema et al, 2019;Molie et al, 2019;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019;Tola et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018;Tulu and Kahissay, 2014) (Table 1 and Figure 1). All of the studies were hospital-based retrospective cohort studies conducted among patients with DR-TB treated under TICs found in different parts of the country.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations